IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) DALAM KETERAMPILAN MENULIS KARANGAN NARASI PELAJARAN BAHASA JERMAN SISWA KELAS XII IPA SMAN 11 SURABAYA - NURVIANA, ITA (LATERNE, 2014)
Writing is an activity that productive and expressive. Writing deals with problems on each discipline of science. It is found that some Schülers feel bored in teaching and learning process when they are using lecturing model. Therefore, teacher needs to apply a model and media of learn which are able to motivate the Schülers. One of the models that can be applied is Problem Based Instruction (PBI) for Schülers of XII IPA 1 SMAN 11 Surabaya. Research question of this study is how the result of Schülers’ narrative text toward learning German language using Problem Based Instruction (PBI) model. This study aims to describe the result of Schülers’ narrative text toward learning German language using Problem Based Instruction (PBI) model. This study is in the form of qualitative. The instrument of this study is Schülers’ test. The data of this study is the result of Schülers’ study. This study is analyzed using writing narrative criteria, formula of class average class, score qualification criteria and total score. The test of Schülers’ study result is in the form of posttest. The conclusion of this study is after Problem Based Instruction (PBI) model was applied in teaching writing narrative text to the Schülers of XII IPA 1 SMAN 11 Surabaya, the result shows that the Schülers’ writing result is better than before. This result can be proved using Schülers’ posttest score result. Key words : narrative text, writing, Problem Based Instruction (PBI) model